Rice price volatility and dietary diversity in Bangladeshi farm households: panel data evidence - Mastura, Tamanna; Alam, Mohammad Jahangir; Begum, Ismat Ara; Iqbal, Md. Asif; McKenzie, Andrew M. (Frontiers in Nutrition, 2026)
IntroductionFood price is an influential factor in gaining food and nutritional security. This paper estimated the association between non-seasonal rice price volatility and dietary diversity in rural Bangladesh.MethodsUsing data from the Bangladesh Integrated Household Survey (2012, 2015, and 2018) combined with World Food Program price data (2012-18), we employed a fixed-effects Poisson regression model to assess how rice price volatility affects household dietary diversity.ResultsThe study found a statistically significant and positive correlation between rice price volatility and dietary diversity. The associations are the same for all income groups across all income quantiles; having more income doesn’t necessarily help households keep eating expensive food. Results show that a 1% increase in rice price volatility is associated with roughly a 0.8% increase in household dietary diversity, suggesting adaptive substitution behavior.DiscussionThe findings suggest that farm households respond to rice price volatility by diversifying their diets rather than reducing dietary quality, likely through substitution toward alternative food groups and diversified production. Policies should balance rice intensification with agricultural diversification to support both caloric adequacy and improved nutrition.